Analysis Of The Economic Dimension Sustainability Of The Na-Oogst Tobaccco Business In Jember - nila afila; Muksin Muksin; Ujang Suryadi (Journal of Agri Socio Economics and Business, 2020)
Na-oogst tobacco commodity is an export commodity that has a role in increasing national income through excise tax. Many factors can influence the decision of farmers to conduct tobacco cultivation in the midst of enormous pressure on tobacco products. This study aims to analyze  the economic dimension sustainability of the na-oogst tobacco business in Jember. The metodology used is Multi Dimensional Scaling (MDS) to analyze sustainability by using 10 atributs. The results of the analysis of the economic dimension show that the na-oogst tobacco business in Jember is categorized as "quite sustainable" with a value of 51,17. The factor that greatly affect the sustainability of the economic dimension and need to be considered is Price Stability with an attribute effect value of 6.77.